Research on Diagnosis and Management of Postgraduates Mental Health Status Based on BP Neural Network - Xie, Jiangning (Frontiers in Public Health, 2022)
As a special group facing the huge pressure of study, employment, life, and other aspects, graduate students have had fierce psychological conflicts. Their mental health status has been greatly affected. Postgraduate mental health problems are related to students' normal life and study and the scientific research work during graduate study. Because of this, this paper uses the BP neural network to establish a diagnostic model for postgraduate mental health status with the dependent variables of SCL-90 psychometric test results to realize the diagnosis of postgraduate' mental health status. The accuracy of the training, validation, and test process of the BP neural network is 98.448, 97.373, 98.128%, and the overall fitting accuracy of the model is 98.273% and the prediction accuracy of graduate mental health is 97.93%. Finally, according to the mental health status of graduate students to ensure the smooth progress of scientific research during graduate students.